The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1021/bi00185a041
|View full text |Cite
|
Sign up to set email alerts
|

NMR Solution Structure of the Isolated N-Terminal Fragment of Protein-G B1 Domain. Evidence of Trifluoroethanol Induced Native-Like .beta.-Hairpin Formation

Abstract: The solution structure of the isolated N-terminal fragment of streptococcal protein-G B1 domain has been investigated in H2O and TFE/H2O solution by CD and NMR to gain insight into the possible role that native beta-hairpin secondary structure elements may have in early protein folding steps. The fragment also has been studied under denaturing conditions (6 M urea), and the resulting NMR chemical shifts were used as a reference for the disordered state. On the basis of CD and NMR data, it is concluded that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
131
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(137 citation statements)
references
References 79 publications
5
131
1
Order By: Relevance
“…At this temperature, hairpin 2 is Ϸ40% native, whereas the helix and hairpin 1 are negligibly stable. This finding agrees with experiments (28,29) that have shown that hairpins 1 and 2 are Ϸ0% and Ͻ42% stable (at pH 6.3, 278 K), and with an independent empirical calculation (30) that predicts Ͻ10% stability for the helix (at pH 7.0, 278 K).…”
supporting
confidence: 91%
“…At this temperature, hairpin 2 is Ϸ40% native, whereas the helix and hairpin 1 are negligibly stable. This finding agrees with experiments (28,29) that have shown that hairpins 1 and 2 are Ϸ0% and Ͻ42% stable (at pH 6.3, 278 K), and with an independent empirical calculation (30) that predicts Ͻ10% stability for the helix (at pH 7.0, 278 K).…”
supporting
confidence: 91%
“…This trace was then complex FFT and the separation between the antiphase components was taken to be the coupling constant. For a few peaks, sine-squared window function shifted by 308 was applied when a stronger window function led to distortion of the peaks 1 H-13 C Gradient-heteronuclear single quantum correlation (HSQC) [24] experiments with sensitivity enhancement were recorded at 0, 27, 36, 45, 54, 63 and 90% TFE to monitor the changes in 13 Ca chemical shifts. Spectral width used for the F1 dimension was 12 000 Hz and 16 scans were added for each of the 600 t 1 increments.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Peptide fragments of GB1 have also been studied in isolation in water and trifluoroethanol, and it has been shown that a peptide comprising the ~3-]34 turn exhibits a significant population of native conformer in water [28,29].…”
Section: Introductionmentioning
confidence: 99%